Recovery of nitrogen-fertilizer from centrate of anaerobically digested sewage sludge via gas-permeable membranes. (December 2020) - Munasinghe-Arachchige, S.P.; Cooke, P.; Nirmalakhandan, N.
Graphical abstract: Highlights: Gas permeable membranes enabled 98 % recovery of NH3 -N from municipal centrate. Achieved flux ranging 21−133 g N/d per m 2 that is better than literature reports. Achieved N-fertilizer yield of 2.1 g ammonium sulfate per liter of centrate. N-fertilizer recovered from centrate met EPA regulations for land application. Abstract: It has been estimated that about 15 % of the current nitrogen-fertilizer demand could be served by recovering the nitrogen-content in domestic sewage. In most sewage treatment plants employing the activated sludge process, the concentrated liquid stream (referred to as centrate) resulting from anaerobic digestion of the waste sludge offers a good opportunity for recovering nitrogen for use as fertilizer. This paper presents a non-pressurized gas-permeable membrane-based approach capable of recovering 98 % of the ammoniacal-nitrogen in the centrate as high purity fertilizer suitable for crop cultivation. In the proposed approach, ammoniacal-nitrogen in the centrate on the feed-side of the hydrophobic gas-permeable membrane is preferentially separated and absorbed into sulfuric acid on the product-side to yield ammonium sulfate solution. A tubular gas-permeable membrane reactor developed in this study was able to recover 21−133 g N/d per m 2 of membrane surface area, which is higher than the typical values of 2–62 g N/d per m 2 reported for more concentrated feeds. The highest yield recorded in this study was 2.1 g of ammonium sulfate per liter of centrate. Scanning electron microscope equipped with an energy dispersive x-ray spectrometer confirmed the presence of nitrogen, oxygen, and sulfur in the recovered fertilizer. Inductively coupled plasma optical emission spectrometer results confirmed that heavy metal levels in the recovered fertilizer were well below the regulatory levels for land application.